2014
DOI: 10.1007/s00535-014-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Streptozocin chemotherapy for advanced/metastatic well-differentiated neuroendocrine tumors: an analysis of a multi-center survey in Japan

Abstract: BackgroundNeuroendocrine tumors (NETs) are believed to be relatively rare and to follow a generally indolent course. However, liver metastases are common in NET patients and the outcome of NET liver metastasis is poor. In Western countries, streptozocin (STZ) has been established as a first-line anticancer drug for unresectable NET; however, STZ cannot be used in daily practice in Japan. The aim of the present study was to determine the status of STZ usage in Japan and to evaluate the effectiveness and safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 17 publications
0
31
0
1
Order By: Relevance
“…With regard to pancreatic NET, a randomized trial indicated the superiority of STZ combined with 5-FU as compared to STZ monotherapy [ 9 , 14 , 15 ]. The toxicities in STZ-based chemotherapy were well tolerated in previous reports [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although the present case was treated successfully with STZ monotherapy and there were no specific toxicities, it was necessary to combine some cytotoxic agents with STZ for additive clinical benefit.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…With regard to pancreatic NET, a randomized trial indicated the superiority of STZ combined with 5-FU as compared to STZ monotherapy [ 9 , 14 , 15 ]. The toxicities in STZ-based chemotherapy were well tolerated in previous reports [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although the present case was treated successfully with STZ monotherapy and there were no specific toxicities, it was necessary to combine some cytotoxic agents with STZ for additive clinical benefit.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies in patients with NET of the pancreas and digestive tract indicated response rates to chemotherapy with STZ in combination with 5-FU or doxorubicin of 27.7–42.0% [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. To our knowledge, there have been no reports focusing on the efficacy of STZ-based chemotherapy in lung NET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, STZ is currently used as a cytotoxic agent for treating pancreatic NET (PanNETs) and GI-NETs. However, its response rate is 40.0% for PanNETs and only 25.0% for GI-NETs [6]. In addition, signi cant improvement of progression-free survival of STZ has not necessarily been established in patients with GI-NETs compared to those with PanNETs, especially in foregut and hindgut NETs [5,7,8].…”
Section: Introductionmentioning
confidence: 99%